KEBIJAKAN PENANGGULANGAN KEBIJAKAN HIV/AIDS MELALUI PENDEKATAN PENTAHELIX DI KOTA CIREBON - Kharisma, Bayu; Ristiza, Chita; Ilyan, Meita; Usrah, Muhammad Jahyul; Ridho Firdaus, Muhammad; Fauziah, Nisa Rahmah; Solecha, Rizka Amalia (Utiliti Project Solution, 2025)
This study aims to determine the involvement of various sectors in handling HIV/AIDS in Cirebon City, identify factors that hinder and encourage the implementation of HIV/AIDS handling in Cirebon City and compile recommendations for strategies that can be implemented in the context of handling HIV/AIDS in Cirebon City. The types of data used in this study are: (1) primary data obtained from the results of interviews with the Mayor represented by the Head of the Cirebon City Health Office through an online seminar on August 1, 2024, and with the Cirebon City KPA via Zoom Meeting. Second, secondary data in this study are from the Cirebon City Health Office in 2024, literature studies by studying various writings through books, journals, theses, and the internet related to the research. The analysis methods used in this study are gap analysis, SWOT analysis and Litmus tests. The results of the analysis show that many factors influence the high prevalence of HIV cases, such as individual behaviour and environmental influences (both social and cultural). The role of WPA is still less than optimal, and the difficulty of reaching and increasing access to services for key population groups and Cirebon City as a transit city are factors that can affect the handling of HIV/AIDS in Cirebon City at this time. However, the Cirebon City government also has things that support the achievement of Three Zeros, including collaboration between the Health Office and KPA, coordination of local governments with NGOs, the availability of HIV/AIDS referral health facilities, the availability of trained human resources, support from national and international programs, and the availability of policies that support handling of HIV/AIDS cases. The Cirebon City Government can utilize community involvement and the use of technology to prevent the spread of HIV/AIDS cases through the following strategies: (1) collaboration of HIV control programs with national and international organizations related to improving HIV services, case finding, ARV treatment, care for PLHIV, and increasing the capacity of officers in the field; (2) developing HIV/AIDS prevention education methods through Inclusive Campaigns and Education utilizing digital platforms; (3) developing data collection strategies and cooperation with transit locations to improve efforts to collect data and prevent HIV cases; (4) implementing direct HIV outreach policies to key population locations to expand access to health services; (5) strengthening monitoring and rapid response systems, especially to identify groups that may be infected from the discovery of new HIV cases. A pentahelix approach between local governments, academics, the business sector, the community, and the media is also an alternative strategy that can be used. Implementing PrEP can reduce the risk of contracting HIV through sexual intercourse and break the chain of HIV transmission.